Study on the learning styles of technology stream students in sri lankan university context - Niroshan, T.S.; Jerentulina, V. (University of Jaffna, 2021)
Learning styles” refers to the way in which different individuals learn. It is a Visual, Auditory and Kinesthetic approach to learn something new. The introduction of Technology Stream became the answer for the passion of youngsters towards the innovative and creative world. Due to the complexity in their university curricula, the failure rate of the students at undergraduate level remains at around 65%. This study focused on identifying the appropriate means to facilitate learning among students. A questionnaire was circulated among the undergraduates from all the Technology Faculties in the Sri Lankan universities in all levels of their academic programme where they can speak about their interests in learning, their preferences while performing the learning activities and their comfortable measures. Based on the data collection, an analytical study was carried out by grading their responses under three major learning style domains. From the survey, auditory and kinesthetic styles of learning shows desirable better response than the visual style. Data obtained shows that auditory and kinesthetic styles are preferred by 34.99% and 34.98% of target group respectively. Nearly 39.97% of the target population express their greater level of learning by auditory and kinesthetic rather than visual styles. The study concluded that auditory and kinesthetic learning styles were greatly preferred by students. It could be inferred that the active involvement and their outgrowth towards learning is boosted by auditory and kinesthetic styles. Since the survey consists of a small target group which shows a remarkable responses, it is clear that the result can be further validated with the entire population. It can be stated that the teaching and learning activities consisting of auditory and kinesthetic styles will result in a noticeable outcome for both the facilitators as well as the learners.
Keywords: Visual; Auditory; Kinesthetic; Technology